The Determination of Tolerances of Some Cotton Genotypes Against Wilt Disease (Verticillium dahliae Kleb.) Under The Ecological Conditions of Diyarbakir - Shimira, Flavien; Temiz, M. Gültekin; Nyırahabımana, Fıldaus; Baran, Nurettin; Mehtap Andırman (My University, 2022)
Verticillium wilt disease in cotton is a soil-borne disease that causes significant yield losses, and it is therefore important to identify disease-resistant genotypes. Current study was carried out in the experimental field of the Faculty of Agriculture, Dicle University (Diyarbakir) in the year 2020 to determine the tolerance levels of some cotton genotypes which contain different characteristics to wilt disease (Verticillium dahliae Kleb.). The experiment area has been naturally infected with Verticillium wilt pathogens. A total of 124 cotton genotypes, including four controls (DP-499, Edessa, ST-468, ES-1), were arranged in five blocks according to the Augmented Design. The indices of stem cross-section and the leaf-disease severity were found significant. The leaf-disease severity varied between 0.12-3.09 at 50-60 % at boll opening period, whilst stem cross-section values ranged between 0.36-2.30. Moreover, a positive correlation was found between the indices. In conclusion, G7, G12, G21, G22, G23, G41, G51, G55, and G101 were determined as tolerant genotypes to Verticillium wilt in terms of examining two parameters.